New record of two species of Rhododendron L. (Ericaceae Juss.) for the flora of Vietnam - Thanh Huong, Nguyen Thi; Hiep, Nguyen Tien (Academia Journal of Biology, 2013)
In the world, the genus Rhododendron L. (Ericaceae Juss.) comprise about 850 species distributed in Asia, Europe and North America. The paper reports two species newly recorded for the flora of Vietnam, such as Rhododendron kendrickii Nutt. and Rhododendron meridionale P. C. Tam, specimens of these species were collected in Ha Giang province. Rhododendron kendrickii Nutt. is closed to R. tanastylum but differed from the later  by having rachis slender, 15-35 mm long, densely tomentose; inflorescence 8-15. Rhododendron meridionale P. C. Tam is closed to R. chunii but differed from the later by having style glabrous. So far, the genus Rhododendron L. consists of 42 species from the flora of Vietnam. The key to 42 Vietnamese species of the genus Rhododendron is also provided.